High Level of Chemokine CCL18 Is Associated With Pulmonary Function Deterioration, Lung Fibrosis Progression, and Reduced Survival in Systemic Sclerosis - Hoffmann-Vold, Anna-Maria; Tennøe, Anders Heiervang; Garen, Torhild; Midtvedt, Øyvind; Abraityte, Aurelija; Aaløkken, Trond Mogens; Lund, May Britt; Brunborg, Cathrine; Aukrust, Pål; Ueland, Thor; Molberg, Øyvind (Chest, 2016)
Markers for early identification of progressive interstitial lung disease (ILD) in systemic sclerosis (SSc) are in demand. Chemokine CCL18, which has been linked to pulmonary inflammation, is an interesting candidate, but data have not been consistent. We aimed to assess CCL18 levels in a large, prospective, unselected SSc cohort with longitudinal, paired data sets on pulmonary function and lung fibrosis. Sera from the Oslo University Hospital SSc cohort (n = 298) and healthy control subjects (n = 100) were analyzed for CCL18 by enzyme immunoassay. High CCL18 (>53 ng/mL) was defined using the mean value plus 2 SD in sera obtained from healthy control subjects as the cutoff. High serum CCL18 was identified in 35% (105 of 298). Annual decline in FVC differed significantly between high and low CCL18 subsets (13.3% and 4.7%; P = .016), as did the annual progression rate of lung fibrosis (0.9% [SD, 2.9] and 0.2% [SD, 1.9]). Highest rates of annual FVC decline > 10% (21%) and annual fibrosis progression (1.2%) were seen in patients with high CCL18 and early disease (< 3 years). In multivariate analyses, CCL18 was associated with annual FVC decline > 10% (OR, 1.1; 95% CI, 1.01-1.11) and FVC < 70% at follow-up (OR, 3.1; 95% CI, 1.08-8.83). Survival analyses showed that patients with high CCL18 had reduced 5- and 10-year cumulative survival compared with patients with low CCL18 (85% and 74%, compared with 97% and 89%, respectively; P = .001). The results from this prospective cohort reinforce the notion that high CCL18 may serve as a marker for early identification of progressive ILD in SSc.